Hofbauer cells morphology and density in placentas from normal and pathological gestations - Charalampos Grigoriadis; Aliki Tympa; Maria Creatsa; Panagiotis Bakas; Angelos Liapis; Agathi Kondi-Pafiti; Georgios Creatsas (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE: In placentas from uncomplicated pregnancies, Hofbauer cells either disappear or become scanty after the fourth to fifth month of gestation. Immunohistochemistry though, reveals that a high percentage of stromal cells belong to Hofbauer cells. The aim of this study was to investigate the changes in morphology and density of Hofbauer cells in placentas from normal and pathological pregnancies. METHODS: Seventy placentas were examined: 16 specimens from normal term pregnancies, 10 from first trimester's miscarriages, 26 from cases diagnosed with chromosomal abnormality of the fetus, and placental tissue specimens complicated with intrauterine growth restriction (eight) or gestational diabetes mellitus (10). A histological study of hematoxylin-eosin (HE) sections was performed and immunohistochemical study was performed using the markers: CD 68, Lysozyme, A1 Antichymotrypsine, CK-7, vimentin, and Ki-67. RESULTS: In normal term pregnancies, HE study revealed Hofbauer cells in 37.5% of cases while immunohistochemistry revealed in 87.5% of cases. In first trimester's miscarriages and in cases with prenatal diagnosis of fetal chromosomal abnormalities, both basic and immunohistochemical study were positive for Hofbauer cells. In pregnancies complicated with intrauterine growth restriction or gestational diabetes mellitus, a positive immunoreaction was observed in 100 and 70% of cases, respectively. CONCLUSIONS: Hofbauer cells are present in placental villi during pregnancy, but with progressively reducing density. The most specific marker for their detection seems to be A1 Antichymotrypsine. It is remarkable that no mitotic activity of Hofbauer cells was noticed in our study, as the marker of cellular multiplication Ki-67 was negative in all examined specimens.